Hubungan Tingkat Pengetahuan Ibu Tentang Makanan Pendamping Asi Dengan Pemberian Makanan Pendamping Asi Pada Bayi 6-12 Bulan Di Puskesmas Bp Nauli Kecamatan Siantar Marihat Kota Pematangsiantar Tahun 2023 - Rehulina Natalia Sembiring; Asnita Sinaga; Isyos Sari Sembiring; Indra Agussamad (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Complementary food for breast milk is the child's second food after breastfeeding. MP-ASI is given to babies who are half a year old or older because breast milk does not meet the child's nutritional needs. MP-ASI feeding must be continuous and varied, starting from fruit, fresh fruit, thick porridge, mashed food, soft food, and finally solid food. The reason for giving MP-ASI at the age of six months is because the child is ready for solid food (Chomaria, 2013). The presentation and arrangement of MP-ASI must be carried out in stages, both in structure and quantity, according to the capacity of the child's stomach. Breast milk only meets the healthy needs of newborn children, but 60% of adult babies 6 years old. Based on the results of bivariate analysis using chi square, the p value = 0.001 (p <0.05) with a confidence level of 95%. This p value statistically shows that there is a relationship between the mother's level of knowledge about complementary foods for breast milk and the provision of complementary foods for babies aged 6-12 months at the BP Nauli Community Health Center, Siantar Marihat District, Pematangsiantar City in 2023 with a p value of 0.001 Providing complementary foods for breast milk , mothers can give food to their babies in stages and provide a variety of foods starting with 1 type of flavor then another, starting with thick porridge, fruit juice, fresh fruit, mashed food, soft food and finally solid food, should be given 3 times a day and Breast milk is still given. According to research results, Widodo (2006) said that in rural communities in Indonesia, the type of MP-ASI that is commonly given to babies before the age of 4 months is 57.3% banana. An initial survey was conducted at the BP Nauli Community Health Center, Siantar Marihat District on mothers who had babies aged 6-12 months. Of the 12 mothers who were interviewed, there were 7 mothers who gave MP-ASI to babies before the age of 6 months, and 5 mothers said that the baby I have been given formula milk since I was born because only a little breast milk comes out. From the results of this background, the author is interested in researching